2020
DOI: 10.1038/s41586-020-3014-1
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor identification and SARS-CoV-2 infection in human distal lung organoids

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
322
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(341 citation statements)
references
References 47 publications
13
322
2
4
Order By: Relevance
“…After excluding immune cells and putative doublets, we identified 30,700 cells that clustered into 17 distinct epithelial, endothelial, and stromal cell types (Figures S4A-S4C). Prior studies have demonstrated that multiple lung cell types express the SARS-CoV-2 entry receptor, ACE2, and the serine protease, TMPRSS2, including epithelial basal, club, and ciliated cells, and alveolar type 1 (AT-1) and 2 (AT-2) cells (Hou et al, 2020;Salahudeen et al, 2020;Sungnak et al, 2020). Human bronchial epithelial cell (HBEC) cultures have shown that ciliated cells may be the initial target of infection, which can later spread to other cell types (Ravindra et al, 2020).…”
Section: Chirp-ms Of Sars-cov-2 Viral Rna In Infected Mammalian Cellsmentioning
confidence: 99%
“…After excluding immune cells and putative doublets, we identified 30,700 cells that clustered into 17 distinct epithelial, endothelial, and stromal cell types (Figures S4A-S4C). Prior studies have demonstrated that multiple lung cell types express the SARS-CoV-2 entry receptor, ACE2, and the serine protease, TMPRSS2, including epithelial basal, club, and ciliated cells, and alveolar type 1 (AT-1) and 2 (AT-2) cells (Hou et al, 2020;Salahudeen et al, 2020;Sungnak et al, 2020). Human bronchial epithelial cell (HBEC) cultures have shown that ciliated cells may be the initial target of infection, which can later spread to other cell types (Ravindra et al, 2020).…”
Section: Chirp-ms Of Sars-cov-2 Viral Rna In Infected Mammalian Cellsmentioning
confidence: 99%
“…It has also been found that human hepatocyte and cholangiocyte organoids show permissive conditions for the culture of SARS-CoV-2 (Chandar et al, 2020). It has been found that hPSC-derived cells/organoids show similar chemokine responses as occurs in COVID-19 tissues ; (Salahudeen et al, 2020).…”
Section: Human Pluripotent Stem Cell-based Platformmentioning
confidence: 93%
“…To reach this goal, they used a 3D organoid in vitro model to simulate distal human lung in which basal stem cells and AT2 cells were cultured. After 26 days of culture , the lung organoid demonstrated the differentiation, and proliferation of different cell types including ACE2 receptor expressing cells [88]. Further, Yang et al designed an in vitro platform using hPSCs, islets, and hepatocyte cells through which they found a relation between diabetes and SARS-CoV-2 infection.…”
Section: Organoids (Biomaterials-based)mentioning
confidence: 99%